Integrating Orange - For better access to vitamin A rich sweetpotato in the Eastern Province of Zambia - International Potato Center (2014)
In its third year, over 5,500 households have been reached with quality sweetpotato planting vines. The project has established a sand-ponic foundation multiplication system with more than 150 recently trained decentralized vine multipliers (DVMs) across eight districts, who are currently maintaining quality orange-fl esh sweetpotato vines for multiplication and distribution next growing season. Fresh root and vine sale campaigns helped raise awareness about the benefi ts of orange-fl eshed sweetpotato.